Attitude and confidence of undergraduate medical programme educators to practice and teach evidence-based healthcare: a cross-sectional survey. Issue 2 (June 2016) - Young, Taryn; Esterhuizen, Tonya M.; Volmink, Jimmy; Clarke, Mike
ABSTRACT: Aim: Medical student educators play critical roles in evidence-based healthcare (EBHC) teaching and learning and as role models practicing EBHC. This study assessed their confidence to practice and teach EBHC, their attitude to EBHC and barriers to practicing and teaching EBHC. Methods: We conducted a cross-sectional online survey of educators of undergraduate medical students at a South African academic institution. STATA 12 was used for quantitative data analysis. Responses to open-ended questions were coded, and further interpretation done using thematic content analysis. Results: Forty two (19%) educators from various departments responded to the invitation sent to everyone formally involved in teaching undergraduate medical students. They had high levels of knowledge and understanding of EBHC. Many had received training in teaching and learning approaches, although EBHC training received was mainly on enabling competencies. Limitations to practicing EBHC included lack of time, clinical workload, limited access to Internet and resources, knowledge and skills. One quarter of the respondents indicated that they teach EBHC. Perceived barriers to teaching EBHC reported related to students (e.g. lack of interest), context (e.g. access to databases) and educators (e.g. competing priorities). Respondents' suggestions for support included reliable Internet access, easy point-of-care access to databases and resources, increasing awareness of EBHC, building capacity to practice and facilitate learning of EBHC and a supportive community of practice. Conclusion: Educators play a critical role in facilitating EBHC learning not just in the classroom, but also in practice. Without adequate support, training and development, they are ill equipped to be the role models future healthcare professionals need.